2012
DOI: 10.1088/1742-6596/381/1/012117
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear physics and space radiation

Abstract: Abstract. Nuclear fragmentation reactions induced by alpha particle projectiles are an important component of the space radiation problem. Inclusive isotopic spectral distributions and double differential cross sections are used as input to the Boltzmann transport equation, which is often solved in many space radiation applications. For alpha particle projectiles, it is found that most of the available experimental data are below the pion threshold. This is a significant validation gap because the important en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(31 citation statements)
references
References 9 publications
0
31
0
Order By: Relevance
“…Nuclear reactions cross sections are key inputs to such transport calculations. Unfortunately, it is precisely the neutron and light ion cross sections that represent the most significant gaps in the experimental database (Nakamura and Heilbronn, 2007;Norbury et al, 2011;. The validation of transport codes makes it important to close these gaps with a program of experimental measurements and associated nuclear reaction model development.…”
Section: Figmentioning
confidence: 99%
“…Nuclear reactions cross sections are key inputs to such transport calculations. Unfortunately, it is precisely the neutron and light ion cross sections that represent the most significant gaps in the experimental database (Nakamura and Heilbronn, 2007;Norbury et al, 2011;. The validation of transport codes makes it important to close these gaps with a program of experimental measurements and associated nuclear reaction model development.…”
Section: Figmentioning
confidence: 99%
“…Previous analyses of experimental data [1][2][3][4] focused on measurement gaps for space radiation. The highest priority measurement recommendations were double differential cross sections for the following ion 2 reactions, He, C, O, Si, Fe + H, C, O, Al, Fe → 1,2,3 H, 3,4 He + X,…”
Section: Introduction and Reviewmentioning
confidence: 99%
“…Space radiation protection and ion therapy applications need reliable nuclear reaction models and transport codes for energetic particles in matter. Neutrons and light ions ( 1 H, 2 H, 3 H, 3 He, and 4 He) are the most important secondary particles produced in space radiation and ion therapy nuclear reactions; these particles penetrate deeply and make large contributions to dose equivalent. Since neutrons and light ions may scatter at large angles, double differential cross sections are required by transport codes that propagate radiation fields through radiation shielding and human tissue.…”
mentioning
confidence: 99%
“…The study of the nuclear fragmentation processes occurring in the interaction of highly energetic ions in matter is of great interest both in basic research (e.g. to improve the understanding of hadronic showers development in the atmosphere) and in applied physics, in particular in cancer therapy and space radiation protection fields [1,2]. Accurate measurements of fragmentation cross sections of light ions interacting with elemental and composite targets are crucials to benchmark and improve the nuclear interaction models implemented in Monte Carlo (MC) simulation codes.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, while the fluences and the total cross sections are currently well described, the production of light fragments and their angular distribution is affected by large uncertainties and different algorithms are predicting yields that can differ up to an order of magnitude. The NASA completed a survey of a large data base [2] of measured nuclear fragmentation cross sections including approximately 50000 data sets, and concluded that several experimental data are missing: accurate measurements of DDCS of light ions in the energy range 100 -1000 MeV/nucleon are, hence, urgently needed to improve nuclear interaction models and are also of great interest in the fields of ion therapy for the treatment of tumors and of space radioprotection.…”
Section: Introductionmentioning
confidence: 99%